Glycine-Histidine-Lysine (GHK) Alleviates Astrocytes Injury of Intracerebral Hemorrhage via the Akt/miR-146a-3p/AQP4 Pathway - Zhang, Heyu; Wang, Yanzhe; Lian, Ling; Zhang, Cheng; He, Zhiyi (Frontiers in Neuroscience, 2020)
Intracerebral hemorrhage (ICH) is a major type of stroke with high morbidity and mortality. Recent studies have shown that Glycyl-l-histidyl-l-lysine (GHK) is a kind of natural human tripeptide which could inhibit inflammation and against neurodegenerative diseases, but neither its role nor the mechanisms in ICH have yet been explicit. In this study, we investigated the effect of GHK on ICH injury. Neurological deficit scores, brain water content, Nissl staining, and aquaporin 4 (AQP4) immunohistochemistry were detected in different groups of ICH rats. The expression of miRNAs was examined by real-time PCR. Inflammatory factors were detected using enzyme-linked immunosorbent assay (ELISA). Cell viability and cell proliferation were detected by Cell Counting Kit-8 (CCK-8). Matrix metalloproteinase 2 (MMP2), matrix metalloproteinase 9 (MMP9), tissue inhibitors of metalloproteinase-1 (TIMP1), AQP4 expression were detected/assessed using western blot. We observed that 5μg/g and 10μg/g of GHK improved neurological recovery in ICH rats, revealed by significantly reducing brain water content, improving neurological deficits, and promoting neuron survival. Besides, GHK alleviated inflammatory reaction and downregulated AQP4 expression. Furthermore, the effects of GHK on astrocyte were associated with the upregulation of miRNA-146a-3p, which partially regulated the expression of AQP4. Our results demonstrated that the phosphatidylinositol 3-kinase (PI3K)/AKT pathway is involved in the GHK-induced up-regulation of miR-146a-3p and miR-146a-3p/AQP4 axis plays a role in the injury following ICH. These findings suggested that GHK may provide a novel therapeutic strategy for ICH.